Declines in traditional marine food intake and vitamin D levels from the 1960s to present in young Alaska Native women. Issue 10 (28th July 2016) - O'Brien, Diane M; Thummel, Kenneth E; Bulkow, Lisa R; Wang, Zhican; Corbin, Brittany; Klejka, Joseph; Hopkins, Scarlett E; Boyer, Bert B; Hennessy, Thomas W; Singleton, Rosalyn
Abstract: Objective: To measure the trends in traditional marine food intake and serum vitamin D levels in Alaska Native women of childbearing age (20–29 years old) from the 1960s to the present. Design: We measured a biomarker of traditional food intake, the δ 15 N value, and vitamin D level, as 25-hydroxycholecalciferol (25(OH)D3 ) concentration, in 100 serum samples from 20–29-year-old women archived in the Alaska Area Specimen Bank, selecting twenty-five per decade from the 1960s to the 1990s. We compared these with measurements of red-blood-cell δ 15 N values and serum 25(OH)D3 concentrations from 20–29-year-old women from the same region collected during the 2000s and 2010s in a Center for Alaska Native Health Research study. Setting: The Yukon Kuskokwim Delta region of south-west Alaska. Subjects: Alaska Native women ( n 319) aged 20–29 years at the time of specimen collection. Results: Intake of traditional marine foods, as measured by serum δ 15 N values, decreased significantly each decade from the 1960s through the 1990s, then remained constant from the 1990s through the present ( F 5, 306 =77·4, P <0·0001). Serum vitamin D concentrations also decreased from the 1960s to the present ( F 4, 162 =26·1, P <0·0001). Conclusions: Consumption of traditional marine foods by young Alaska Native women dropped significantly between the 1960s and the 1990s and was associated with a significant decline in serum vitamin D concentrations. Studies are needed to evaluate the promotion of traditional marine foods and routine vitamin D supplementation during pregnancy for this population.